2023
DOI: 10.1155/2023/8483325
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Specific Peptidase 8 Modulates Cell Proliferation and Induces Cell Cycle Arrest and Apoptosis in Breast Cancer by Stabilizing Estrogen Receptor Alpha

Abstract: Breast cancer (BC) is the most common neoplastic and lethal malignancy in women. Although antiendocrine therapy is the main treatment for estrogen receptor alpha (ERα)-positive BC, the development of resistance is a major clinical complication. In this study, we aimed to explore the role of ubiquitin-specific peptidase 8 (USP8) in ERα signaling and identify potential targets for endocrine resistance. Public databases were used to analyze USP8 expression, prognosis, clinical characteristics, and immune cell inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…USP8 is a member of the USPs subfamily, widely expressed and distributed in human cells and tissues and a key subunit of the human Spt-Ada-Gcn5 acetyltransferase (hSAGA) transcription cofactor complex [35]. Previous research reported that USP8 was frequently high-expressed and acted as oncogene in multiple cancers [5][6][7]. However, the function of USP8 in KIRC needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP8 is a member of the USPs subfamily, widely expressed and distributed in human cells and tissues and a key subunit of the human Spt-Ada-Gcn5 acetyltransferase (hSAGA) transcription cofactor complex [35]. Previous research reported that USP8 was frequently high-expressed and acted as oncogene in multiple cancers [5][6][7]. However, the function of USP8 in KIRC needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-speci c protease (USP) family is the largest subfamily of the deubiquitylating enzyme (DUB) family. As a member of USP family, USP8 plays an important role in cell proliferation, migration, invasion and it also regulates protein levels, and the depletion of USP8 stimulates cell cycle arrest and apoptosis [5]. There is increasing evidence suggests that abnormal expression of USP8 can affect diverse signaling pathways in different types of tumors and lead to cancer progression, metastasis, and low survival rate [6][7].…”
mentioning
confidence: 99%
“…Recent studies have underscored that immune infiltration of tumor cells plays a pivotal role in cancer progression and outcomes ( 17 , 18 ). In light of this, leveraging the B-cell specific long non-coding RNA (lncRNA) signature, we employed a suite of algorithms, namely QUANTISEQ ( http://icbi.at/quantiseq ), CIBERSORT ( https://cibersortx.stanford.edu ), XCELL ( https://comphealth.ucsf.edu/app/xcell ), CIBERSORT abs.mode ( https://cibersortx.stanford.edu ), EPIC ( http://epic.gfellerlab.org ), TIMER ( https://cistrome.shinyapps.io/timer ), and MCP-counter ( https://github.com/ebecht/MCPcounter ), to gauge the extent of immune cell infiltration across high- and low-risk groups.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that ER promotes an estrogen-independent, E2F-mediated transcriptional program in human breast cancer cells [32]. Additionally, the G2M checkpoints and mitotic spindle play direct roles in the cell cycle, which can be regulated by estrogen binding and subsequent activation of signaling pathways that promote cell cycle progression [33][34][35]. The remaining two gene sets are also directly associated with estrogen response.…”
Section: Association Between Cosinet Score and Survival Outcomes In B...mentioning
confidence: 99%